13b-6=3b+4

Simple and best practice solution for 13b-6=3b+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13b-6=3b+4 equation:


13b-6=3b+4

We simplify the equation to the form, which is simple to understand
13b-6=3b+4

We move all terms containing b to the left and all other terms to the right.
+13b-3b=+4+6

We simplify left and right side of the equation.
+10b=+10

We divide both sides of the equation by 10 to get b.
b=1

See similar equations:

| -2(-7k+5)+9=-13 | | 229-4x=32x+17 | | 1/9x^2+2/3x-3=0 | | 6-8x=114-29x | | x/5+x/7=8/7 | | 8(x+2)-2=22-4x-8+12x | | 5x+5=10x-20 | | 9x-5y=18 | | 12r^2=27+27r | | 2x+5=115-10x | | 12+2x=2-4x | | -4(t-1)+9t=8t-8 | | 6c^2+9c/3c | | -5(t-1)+7t=6t-6 | | n-14=16 | | 51-3x=10x+22 | | -5+6(x-3)=15x+3-9x | | -9(t+2)=54 | | 0.5x-0.3(10-3x)=-0.6(x-5) | | 13=13 | | 1/6x-3=5 | | -7/8v=35 | | 3+y/2=3y/4-2 | | x^2+10x+98=0 | | 6+6x=42+x | | -14-9=12 | | 6(a-7)+20=2(a-7) | | 5(5x-3)+5=-9 | | -22u+-1x= | | 9x-3=6x+39 | | 4-4x=-2x-12 | | 18-3x=-9x |

Equations solver categories